2017
DOI: 10.1007/s12185-017-2263-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the study of immunodeficiency and DNA damage response

Abstract: DNA breaks can be induced by exogenous stimuli or by endogenous stress, but are also generated during recombination of V, D, and J genes (V(D)J recombination), immunoglobulin class switch recombination (CSR). Among various DNA breaks generated, DNA double strand break (DSB) is the most deleterious one. DNA damage response (DDR) is initiated when DSBs are detected, leading to DNA break repair by non-homologous end joining (NHEJ). The process is critically important for the generation of diversity for foreign an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…In immunoglobulin class switch recombination, a DSB is induced by the activation of a cytidine deaminase before broken ends are repaired by NHEJ or MMR. Any deficiency in one of the effectors of these repair complexes impairs the generation of IgG diversity to fight foreign antigens (acquired immunity), and leads to immunodeficiency at various degrees or hyper-IgM syndrome [151].…”
Section: Immune Diseases and Inflammationmentioning
confidence: 99%
“…In immunoglobulin class switch recombination, a DSB is induced by the activation of a cytidine deaminase before broken ends are repaired by NHEJ or MMR. Any deficiency in one of the effectors of these repair complexes impairs the generation of IgG diversity to fight foreign antigens (acquired immunity), and leads to immunodeficiency at various degrees or hyper-IgM syndrome [151].…”
Section: Immune Diseases and Inflammationmentioning
confidence: 99%
“…Researches showed that nuclear Hsp90 could bind to MRN complex and maintain its activity [ 39 , 40 ], others found that Hsp90 could interact with DDR proteins [ 26 ] and regulate the recruitment of 53BP1 to DSBs [ 41 ], suggesting Hsp90 may be related to DNA damage repair but the specific mechanism remains to be studied. Rad50 and Ku80 are key proteins for DSBs repair [ 42 ], which were downregulated after lamin-A further knockdown in our previous research [ 13 ]. Here, the effect of Hsp90 inhibition on DSBs repair was further studied.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the current study shows normal numbers of B and T cells in adult animals without BMT. More than a dozen molecules are involved in CSR ( 31 , 64 ), including those involved in the DNA damage response, components of the NHEJ pathway, and factors that induce topological changes in the nuclear architecture ( 48 ), and it is possible that Lsh promotes NHEJ activity by modulating known pathways. Interestingly, CSR of IgG2b was not significantly affected in Lsh-deficient B cells.…”
Section: Discussionmentioning
confidence: 99%